The efficacy and cost‐effectiveness of a family‐based economic empowerment intervention (Suubi + Adherence) on suppression of HIV viral loads among adolescents living with HIV: results from a Cluster Randomized Controlled Trial in southern Uganda. Issue 6 (27th June 2021) - Tozan, Yesim; Capasso, Ariadna; Sun, Sicong; Neilands, Torsten B; Damulira, Christopher; Namuwonge, Flavia; Nakigozi, Gertrude; Mwebembezi, Abel; Mukasa, Barbara; Sensoy Bahar, Ozge; Nabunya, Proscovia; Mellins, Claude A; et al.
Abstract: Introduction: Evidence from low‐resource settings indicates that economic insecurity is a major barrier to HIV treatment adherence. Economic empowerment (EE) interventions have the potential to improve adherence outcomes among adolescents living with HIV (ALWHIV) by mitigating the effects of poverty. This study aims to assess the efficacy and cost‐effectiveness of a savings‐led family‐based EE intervention, Suubi + Adherence, aimed at improving antiretroviral therapy (ART) adherence outcomes ALWHIV in Uganda. Methods: Adolescents (mean age 12 years at enrolment; 56% female) receiving ART for HIV at 39 health centres were randomized to Suubi + Adherence intervention (n = 358) or bolstered standard of care (BSOC; n = 344). A difference‐in‐differences analysis was employed to assess the change in the proportion of virally suppressed adolescents (HIV RNA viral load <40 copies/mL) over 24 months. The cost‐effectiveness analysis examined how much the intervention cost to virally suppress one additional adolescent relative to BSOC from the healthcare provider perspective. Results: At 24 months, the intervention was associated with an 8.85‐percentage point [95% confidence interval (CI) 0.80 to 16.90 percentage points] increase in the proportion of virally suppressed adolescents between the study arms ( p  = 0.032). Per‐participant costs were US$177 and US$263 for the BSOC and intervention groups respectively. The incremental cost of virally suppressing one additional adolescent was estimated at US$970 [95% CI, US$508 to 10, 725] over two years. Conclusions: Our results support the integration of family‐based EE interventions into adherence‐support strategies as part of routine HIV care in low‐resource settings to address the underlying economic drivers of poor ART adherence among ALWHIV. Moreover, per‐participant costs to achieve viral suppression do not seem prohibitive compared to other community‐based adherence interventions targeted at ALWHIV in low‐resource settings. Further research on combination interventions at the nexus of economic security and HIV treatment and care is needed to inform the development of feasible and scalable HIV policies and programmes.